A non-invasive specimen collection method and a novel simian foamy virus (SFV) DNA quantification assay in New World primates reveal aspects of tissue tropism and improved SFV detection. - Cláudia P Muniz; HaoQiang Zheng; Hongwei Jia; Liliane T F Cavalcante; Anderson M Augusto; Luiz P Fedullo; Alcides Pissinatti; Marcelo A Soares; William M Switzer; André F Santos (PLoS ONE)
Simian foamy viruses (SFVs) co-evolved with a wide range of Old World and New World primates (OWPs and NWPs, respectively) and occasionally transmit to humans. Previous studies of OWPs showed that the predominant site of SFV replication is the oral mucosa. However, very little is known about SFV viral loads (VLs) in the oral mucosa or blood of NWPs. NWPs have smaller body sizes, limiting collection of sufficient whole blood volumes to molecularly detect and quantify SFV. Our study evaluated the use of noninvasively collected buccal swabs to detect NWP SFV compared with detection in blood using a new NWP SFV quantitative PCR (qPCR) assay. Buccal and blood samples were collected from 107 captive NWPs in Brazil comprising eleven distinct genera at the Primate Center of Rio de Janeiro (n = 58) and at Fundação Jardim Zoológico da Cidade do Rio Janeiro (n = 49). NWP SFV western blot (WB) testing was performed on a subset of animals for comparison with PCR results. The qPCR assay was validated using distinct SFV polymerase sequences from seven NWP genera (Callithrix, Sapajus, Saimiri, Ateles, Alouatta, Cacajao and Pithecia). Assay sensitivity was 20 copies/106 cells, detectable in 90% of replicates. SFV DNA VLs were higher in buccal swabs (5 log copies/106 cells) compared to peripheral blood mononuclear cells (PBMCs) (3 log copies/106 cells). The qPCR assay was also more sensitive than nested PCR for detection of NWP SFV infection and identified an additional 27 SFV-infected monkeys of which 18 (90%) were WB-positive and three that were WB-negative. We show the utility of using both blood and buccal swabs and our new qPCR assay for detection and quantification of diverse NWP SFV, which will assist a better understanding of the epidemiology of SFV in NWPs and any potential zoonotic infection risk for humans exposed to NWPs.